Decentralization Policy Implementation in Malang City's Public Service - Putra, I Made Arie Widyasthana Wartana; Wardhani, Aghniya Salsabila (Journal of Transformative Governance and Social Justice, 2024)
Decentralization policy in Indonesia aims to improve the quality of public services through governance that is closer to theÂ community. However, the implementation of this policy still faces many challenges, including a lack of awareness of public service programs implemented by local governments. This article uses the Literature Review method, which is a method carried out by reading various literature in the form of books or previous journal articles as a source for articles in order to obtain a theoretical basis for the problem being studied. The results of the article show that the low level of public knowledge regarding making e-KTP in Malang City is influenced by several factors. First, communication between local government and the community is less effective in socializing the e-KTP program. Second, limited human resources and budget allocated for socialization programs. Third, some public officials still lack the desire or commitment to provide clear information to the public. Fourth, the bureaucracy is still not optimal in coordinating the implementation of the e-KTP program at various levels. The results of this article provide important implications for the Malang City Government in its efforts to increase public knowledge about public services for making e-KTP. Recommendations given include improving communication strategies to make them more effective, allocating adequate resources, increasing the capacity and commitment of state civil servants, and improving bureaucratic structures to improve coordination between levels.